A scalable serology solution for profiling humoral immune responses to SARS‐CoV‐2 infection and vaccination. Issue 3 (23rd March 2022) - Colwill, Karen; Galipeau, Yannick; Stuible, Matthew; Gervais, Christian; Arnold, Corey; Rathod, Bhavisha; Abe, Kento T; Wang, Jenny H; Pasculescu, Adrian; Maltseva, Mariam; Rocheleau, Lynda; Pelchat, Martin; et al.
Abstract: Objectives: Antibody testing against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has been instrumental in detecting previous exposures and analyzing vaccine‐elicited immune responses. Here, we describe a scalable solution to detect and quantify SARS‐CoV‐2 antibodies, discriminate between natural infection‐ and vaccination‐induced responses, and assess antibody‐mediated inhibition of the spike‐angiotensin converting enzyme 2 (ACE2) interaction. Methods: We developed methods and reagents to detect SARS‐CoV‐2 antibodies by enzyme‐linked immunosorbent assay (ELISA). The main assays focus on the parallel detection of immunoglobulin (Ig)Gs against the spike trimer, its receptor binding domain (RBD) and nucleocapsid (N). We automated a surrogate neutralisation (sn)ELISA that measures inhibition of ACE2‐spike or ‐RBD interactions by antibodies. The assays were calibrated to a World Health Organization reference standard. Results: Our single‐point IgG‐based ELISAs accurately distinguished non‐infected and infected individuals. For seroprevalence assessment (in a non‐vaccinated cohort), classifying a sample as positive if antibodies were detected for ≥ 2 of the 3 antigens provided the highest specificity. In vaccinated cohorts, increases in anti‐spike and ‐RBD (but not ‐N) antibodies are observed. We present detailed protocols for serum/plasma or dried blood spots analysis performed manually and on automated platforms. The snELISA can be performed automatically at single points, increasing its scalability. Conclusions: Measuring antibodies to three viral antigens and identify neutralising antibodies capable of disrupting spike‐ACE2 interactions in high‐throughput enables large‐scale analyses of humoral immune responses to SARS‐CoV‐2 infection and vaccination. The reagents are available to enable scaling up of standardised serological assays, permitting inter‐laboratory data comparison and aggregation. Abstract : We developed scalable serology assays to detect and quantify SARS‐CoV‐2 antibodies, discriminate between natural infection‐ and vaccination‐induced responses, and assess antibody‐mediated inhibition of the spike‐angiotensin converting enzyme 2 (ACE2) interaction. This serology solution enables large‐scale analyses of humoral immune responses to SARS‐CoV‐2 infection and vaccination permitting inter‐laboratory data comparison and aggregation.